RELEVANSI PERDA NOMOR 3 TAHUN 1991 DALAM PEMBANGUNAN PARIW ISATA BUDAYA BALI - Hadi Sukarno, Teguh (Pusat Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Nusa Dua Bali, 2007)
The Government of Bali decided that culture tourism concepts were viewedas the ideology, spirit, guidelines, framework and solutions in developing tourismin Bali. These decisions were then legitimized in a form of provincialrules